Tradition and Culture Acculturation Between Batak and Malay Through Marriage in Medan Labuhan - Adira Hamdi; Nursapiah Harahap (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
Destination from research this is for knowing acculturation culture Malay and Batak through wedding in the city of Medan, Medan Labuhan sub district. Indonesia is a country that is rich in culture so that fusion between culture is very possible happen. Blend culture so that shape culture new called with acculturation culture. Study this use methodology descriptive qualitative with data collection techniques using interviews, observations and documentation. Result of study article this show that no occur significant acculturation in Medan Labuhan District consequence wedding. Customs and culture no changed same once to keep sustainability, essence and existence of each culture. Changes that happened only difference habit like procession inclined marriage more short with maximizing custom that is mandatory.